2003
DOI: 10.1099/vir.0.19107-0
|View full text |Cite
|
Sign up to set email alerts
|

Newcastle disease virus nucleocapsid protein: self-assembly and length-determination domains

Abstract: The nucleocapsid protein (NP) of Newcastle disease virus expressed in E. coli assembled as ring-and herringbone-like particles. In order to identify the contiguous NP sequence essential for assembly of these particles, 11 N-or C-terminally deleted NP mutants were constructed and their ability to self-assemble was tested. The results indicate that a large part of the NP N-terminal end, encompassing amino acids 1 to 375, is required for proper folding to form a herringbone-like structure. In contrast, the C-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 22 publications
3
24
0
Order By: Relevance
“…Constructs in which most or all of the tail was removed (1 to 375, 1 to 400, and 1 to 425) produced the longest particles. Very similar observations were recently reported for the Newcastle disease virus N protein (28).…”
Section: Discussionsupporting
confidence: 75%
“…Constructs in which most or all of the tail was removed (1 to 375, 1 to 400, and 1 to 425) produced the longest particles. Very similar observations were recently reported for the Newcastle disease virus N protein (28).…”
Section: Discussionsupporting
confidence: 75%
“…3 to 5). Several studies have demonstrated that the N-terminal regions of the NP/N molecules of paramyxoviruses are generally important for NP-NP (N-N) interaction (1,4,19,20,27,29), therefore our data support the functional conservation of this region of NP for NP-NP interactions among the members of Mononegavirales. The fact that a small region (residues 230 to 370) of the N terminus of Ebola virus NP shares appreciable amino acid homology with the NPs/Ns of paramyxoviruses and, to a lesser extent, with those of rhabdoviruses (34) further supports this notion.…”
Section: Discussionsupporting
confidence: 67%
“…2c), demonstrating that the R2 and R3 regions are interchangeable with those from NDV and the differences in the amino acid residues in these regions (Fig. 3) are unlikely to be involved in NiV capsid formation.Many studies have shown that paramyxovirus nucleocapsid proteins self-assemble into herringbone-like particles when expressed in a heterologous system in the absence of the viral proteins (Buchholz et al, 1993; Curran et al, 1993; Bankamp et al, 1996;Krishnamurthy & Samal, 1998;Seal et al, 2002;Kho et al, 2003). However, the contiguous regions of the N protein required for capsid assembly are poorly characterized in Henipavirus.…”
mentioning
confidence: 99%